Processus multi-acteurs pour gerer l’utilisation des eaux usees en agriculture. In French. [Multi-stakeholder processes for managing wastewater use in agriculture]. - Evans, Alexandra E.V.; Raschid-Sally, Liqa; Cofie, Olufunke O. (2011)
Wastewater use in agriculture is a complex phenomenon since it transcends typical sectoral and geographical policy and planning boundaries, and is influenced by opinions and perceptions. Planning for wastewater use typically requires the involvement of a number of government agencies covering health, water, sanitation, agriculture and irrigation, as well as researchers, community groups and the private sector. Where wastewater use is already taking place spontaneously and unofficially, how can these stakeholders come together to improve the management of the system to maximize the livelihoods benefits while minimizing impacts on health and the environment? One option is the formation of multi-stakeholder platforms, which provide a space for stakeholders to share opinions and seek negotiated solutions in an open and ?level? environment. How effective these are, what outcomes can be expected, and how they can be improved are all questions that are still being asked. This chapter presents three case studies in which multi-stakeholder processes were used to improve wastewater management for urban agriculture. Although differences were observed, there were several cross-cutting lessons. A critical factor is the starting point, including an agreed definition of the problem to be addressed, negotiated goals and a management structure that is acceptable to all stakeholders. When multi-stakeholder processes are externally initiated, as with those reviewed here, it is essential that project priorities are commensurate with local priorities. Finding an institutional home and anchor agency an improve long-term sustainability but care must be taken in considering how this impacts on existing power structures. Participation and representation greatly influence the effectiveness of the process and much may need to be done to support this, for example by strengthening local community groups. A factor that appears to significantly improve participation and engagement is having tangible outputs, which demonstrate to stakeholders the potential of multi-stakeholder platforms.